Study of environmental and genetic factors determining warfarin toxicity - Sahay, Ravindra Nath; Salagre, Kaustubh Dilip; Dedhia, Khushali Rajesh (International Journal of Research in Medical Sciences, 2017)
Background: Warfarin is widely used anticoagulant in treatment and prevention of thrombosis. Despite its common use, warfarin can be associated with bleeding complications because of its narrow therapeutic index. A review of many studies show average yearly rates of warfarin related bleeding as high as 0.5% , 4.9% , 15% for fatal, major, minor bleeding complications. The study is to determine age, gender, pharmacogenetics, drugs influencing warfarin toxicity in Indian patients. Methods: Observational and cross-sectional study was conducted over period of 1 year after obtaining institutional ethics committee permission. Written and informed consent was taken from patients admitted in tertiary care hospital who fulfilled inclusion and exclusion criteria. Results: Most common age for Warfarin toxicity in our study was between 30 to 39 years (22.5%) with mean of 42.9 years. Bleeding risk was higher in elderly with 14 out of 26 patients with age >50 years had bleeding manifestations. Toxicity was more prevalent in female (60%). 40% patients were on drugs interacting with warfarin; NSAIDS (Nonsteroidal Anti-Inflammatary Drug) and antibiotics were the most common interacting drugs. In our study, 17.5% patients had acute liver disease and one patient had deranged creatinine (2.6). 40% of patients had VKORC1 variants and 35% of patients had CYP2C9 variants. Maximum patients developed toxicity within 15-30 days of initiation of warfarin. Conclusions: Warfarin toxicity has multifactorial cause. Drugs and Genetic variation are most common factors influencing warfarin toxicity. Warfarin toxicity has low mortality rate, although it increases with (International Normalised Ratio) INR>10 and with increasing age.